Pertanggungjawaban Pidana Pada Kasus Kecelakaan Lalu Lintas Yang Mengakibatkan Kematian Atas Dampak Kerusakan Jalan (Studi Kasus Putusan Pengadilan Negeri Rembang Nomor 129/Pid.Sus/2019/PN Rbg) - B.A.S. Faomasi Jaya Laia; Madiasa Ablisar; Alvi Syahrin; M. Ekaputra (Iuris Studia: Jurnal Kajian Hukum, 2021)
The problem of traffic accidents that cause death due to road damage is a problem that is always prominent from time to time. Of course, it needs to be studied in the aspect of criminal liability to resolve if there is a legal event in question occurs. The research method used in this research is normative juridical. The results showed that awave of traffic accidents that occurred due to road damage here found there were 2 (two) pihak which will basically receive the consequences ofroad users(community)  both victims and perpetrators,for  road organizers (whodeal withroad repairs / road repairs, namely the Public Works Office in each region),  Criminalliability for the occurrence of traffic accidents that result in death caused by road damage,can be charged to different parties because of their nature is kasuistis. Rembang District Court Decision No. 129 / Pid.Sus / 2019 / PN Rbg  basically the judge's decision can be said to be appropriate to say the defendant has been negligent because he was not careful and vigilant when driving on damaged roads / potholes